Pelatihan Literasi Budaya dan Digital bagi Generasi Muda dalam Rangka Pelestarian Warisan Budaya Lokal di Kecamatan Taniwel - Touwe, Sem; Ufie, Agustinus; Maisuri, Tama (Universitas Pattimura, 2025)
This community service activity was conducted in Taniwel District, West Seram Regency, over four days involving 45 young participants from several villages. It aimed to address the challenges of low cultural and digital literacy that threaten the continuity of local cultural heritage. Using a Participatory Action Learning approach, the program strengthened youth capacity to integrate cultural values with digital competencies through a participatory and collaborative learning process. The community, traditional leaders, and educational institutions were actively engaged throughout the stages to ensure the integration of cultural values and technology. The results indicated a significant improvement in participants’ ability to document, edit, and publish cultural content digitally, alongside increased awareness of preserving their cultural identity. This program produced a culture-based empowerment model adaptive to technological advancement, empowering youth as active agents in cultural preservation through digital media. The implications highlight the necessity of policy support and digital infrastructure development to sustain community-based cultural preservation initiatives.